The multiple intelligences and their effect in the teaching learning process of the english language with the students of 1st, 2nd and 3rd years of high school curriculum at Vicente Anda Aguirre high school, academic year 2012 – 2013 - Bravo Ludeña, Cristyan Paul (2015)
The present research entitle has as its main objective to find out the influence of the Multiple Intelligences in the Teaching Learning Process of the English Language Learning in students of the 1st, 2nd and 3rd years of Bachillerato at ” Vicente Anda Aguirre” High School, Academic year 2012 – 2013. The scientific, descriptive, and explicative methods were used to carry out the research. The survey applied to both teachers and students of the institution was related to the stated hypotheses and the information gotten was processed and represented on the corresponding tables and graphs. There are certain multiple intelligences that facilitate the students’ English language learning. However there is a little application of strategies and techniques of the multiple intelligences that stimulate the English language learning.